Correction to: Cutaneous protothecosis in a dog successfully treated with oral itraconazole in pulse dosing (Acta Veterinaria Scandinavica, (2023), 65, 1, (7), 10.1186/s13028-022-00662-x) - Gmyterco, Vanessa Cunningham; Jagielski, Tomasz; Baldasso, Gustavo; Bacher, Louise Helene; Ribeiro, Marcio Garcia [UNESP]; de Farias, Marconi Rodrigues (Springer Nature, 2023)
Following publication of the original article [1], the authors reported an error in postal code of Affiliation 2. The correct postal code is 02-926. Moreover, the authors detected a typo in the caption of Fig. 1. The updated caption is given below and the changes have been highlighted in bold typeface. Figure 1 Cutaneous lesions caused by Protothecawickerhamii in a dog. Dog, female, 18 months old with cutaneous protothecosis: a eroded-ulcerative and exudative nasolabial plaques; b erythematous, ulcerative and painful lesions on foot pad. The original article [1] has been updated.